Adjuvant hyperthermic intraperitoneal chemotherapy in patients with locally advanced colon cancer (COLOPEC): a multicentre, open-label, randomised trial. (October 2019) - Klaver, Charlotte E L; Wisselink, Daniel D; Punt, Cornelis J A; Snaebjornsson, Petur; Crezee, Johannes; Aalbers, Arend G J; Brandt, Alexandra; Bremers, Andre J A; Burger, Jacobus W A; Fabry, Hans F J; Ferenschild, Floris; Festen, Sebastiaan; et al.
Summary: Background: Nearly a quarter of patients with locally advanced (T4 stage) or perforated colon cancer are at risk of developing peritoneal metastases, often without curative treatment options. We aimed to determine the efficacy of adjuvant hyperthermic intraperitoneal chemotherapy (HIPEC) in patients with locally advanced colon cancer. Methods: This multicentre, open-label trial was done in nine hospitals that specialised in HIPEC in the Netherlands. Patients with clinical or pathological T4N0–2M0-stage tumours or perforated colon cancer were randomly assigned (1:1), with a web-based randomisation application, before resection of the primary tumour, to adjuvant HIPEC followed by routine adjuvant systemic chemotherapy (experimental group) or to adjuvant systemic chemotherapy alone (control group). Patients were stratified by tumour characteristic (T4 or perforation), age (<65 years or ≥65 years), and surgical approach of the primary tumour resection (laparoscopic or open). Key eligibility criteria included age between 18 and 75 years, adequate clinical condition for HIPEC, and intention to start adjuvant systemic chemotherapy. Patients with metastatic disease were ineligible. Adjuvant HIPEC consisted of fluorouracil (400 mg/m 2 ) and leucovorin (20 mg/m 2 ) delivered intravenously followed by intraperitoneal delivery of oxaliplatin (460 mg/m 2 ) for 30 min at 42°C, delivered simultaneously or within 5–8 weeks after primary tumour resection. In all patients without evidence of recurrent disease at 18 months, a diagnostic laparoscopy was done. The primary endpoint was peritoneal metastasis free-survival at 18 months, measured in the intention-to-treat population, with the Kaplan-Meier method. Adverse events were assessed in all patients who received assigned treatment. This study is registered withClinicalTrials.gov, numberNCT02231086 . Findings: Between April 1, 2015, and Feb 20, 2017, 204 patients were randomly assigned to treatment (102 in each group). In the HIPEC group, two patients withdrew consent after randomisation. In this group, 19 (19%) of 100 patients were diagnosed with peritoneal metastases: nine (47%) during surgical exploration preceding intentional adjuvant HIPEC, eight (42%) during routine follow-up, and two (11%) during diagnostic laparoscopy at 18-months. In the control group, 23 (23%) of 102 patients were diagnosed with peritoneal metastases, of whom seven (30%) were diagnosed by laparoscopy at 18-months and 16 during regular follow-up (therefore making them ineligible for diagnostic laparoscopy). In the intention-to-treat analysis (n=202), there was no difference in peritoneal-free survival at 18-months (80·9% [95% CI 73·3–88·5] for the experimental group vs 76·2% [68·0–84·4] for the control group, log-rank one-sided p=0·28). 12 (14%) of 87 patients who received adjuvant HIPEC developed postoperative complications and one (1%) encapsulating peritoneal sclerosis. Interpretation: In patients with T4 or perforated colon cancer, treatment with adjuvant HIPEC with oxaliplatin did not improve peritoneal metastasis-free survival at 18 months. Routine use of adjuvant HIPEC is not advocated on the basis of this trial. Funding: Organization for Health Research and Development and the Dutch Cancer Society.